The Impact of a Web-Based Educational Initiative in Malang Regency: Enhancing Late Onset Hypogonadism (LOH) Awareness Through Community Service - Irnandi, Dicky Faizal; Hanggara, Dian Sukma; Khotimah, Husnul; Rifqi, Mochamad Shalahudin; Evangelista, Bernike Azza; Gonius, Andry; Kusdijanto, Amanda Yuanita (Indonesian Andrology and Biomedical Journal, 2023)
Late Onset Hypogonadism (LOH), commonly known as andropause, poses significant hormonal challenges for elderly men, impacting their overall quality of life. With testosterone levels naturally declining from the age of 30 and accelerating beyond 40, this hormonal imbalance can manifest in symptoms that degrade the well-being of men. This community service initiative aimed to improve understanding and early detection of LOH among the Indonesian male population. A web-based application, "Skrining Andropause" was developed, allowing individuals to self-assess their LOH risk through the validated Androgen Deficiency in the Aging Male (ADAM) questionnaire. The application included educational videos to enhance public awareness of andropause. Pre- and post-tests were conducted as success indicators, involving 40 male participants aged 40 and above in Malang Regency. Statistical analyses were performed to assess the impact on knowledge related to andropause across different educational backgrounds and age groups. Significant improvement in public understanding of andropause was observed (p=0.000). While educational backgrounds were not significantly associated with initial knowledge (p=0.100), nor with the increase in pre-to-post-test scores (p=0.100). When associating age groups with initial knowledge (p=0.308) and the increase in pre-to-post-test scores (p=0.308), results were not statistically significant. The observed substantial improvement in andropause understanding highlights the efficacy of our educational approach. Respondents, irrespective of educational background, shared a baseline understanding, with those with basic education showing the most significant improvement. Notably, the youngest age group displayed the highest baseline awareness. However, the oldest age group exhibited the least responsiveness to our educational media.